PENGARUH MOTIF BERWIRAUSAHA DAN JIWA KEWIRAUSAHAAN TERHADAP KINERJA USAHA DENGAN KOMITMEN PELAKU USAHA SEBAGAI VARIABEL INTERVENING PADA INDUSTRI TAHU & TEMPE DI KOTA PEKANBARU - Vony, Karlina Rossa; Susi, Hendriani; Dian, Novrianti Puspita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
This research aims to determine the influence of entrepreurial motives andentrepreneurial spirit on business performance with the commitment of businessactors as an intervening variable in the tofu & tempe industry in Pekanbaru City.Data was obtained by distributing questionnaires to 50 respondents. The dataanalysis method for this research uses SPSS. The research results show thatentrepreneurial motives have a positive effect on the performance of businessactors. The entrepreneurial spirit influences business performance. Thecommitment of business actors has a positive effect on the performance ofbusiness actors. Entrepreneurial motives have a positive effect on the commitmentof business actors. The entrepreneurial spirit has a positive effect on thecommitment of business actors. Entrepreneurial motives do not have a positiveeffect on business performance. The influence of an entrepreneurial spirit has apositive effect on business performance. Keywords: Entrepreneurial Motives, Entrepreneurial Spirit, Commitment ofBusiness Actors, Business Performance.